Rating the resilience of transport infrastructure project delivery: the case of roads. Issue 1 (10th December 2018) - Roumboutsos, Athena; Pantelias, Aristeidis
Abstract : Transport infrastructure project delivery resilience has been defined and approached through the assessment of a project's likelihood to reach prespecified performance targets. In this assessment, infrastructure project delivery is considered as a system and its key elements are represented through system indicators. Qualitative and quantitative (indicator) analysis of 86 EU infrastructure projects allowed the identification of indicator combinations and their value ranges that capture the likelihood of achieving four key output targets – that is, cost and time to construction completion and actual against forecast traffic and revenues. Indicators have also been classified as actionable (or not) – that is, allowing (or not) the possibility to improve the likelihood of reaching prespecified project delivery targets. Based on indicator analysis findings, a novel methodology has been proposed for rating the likelihood of transport infrastructure projects to achieve their performance targets, through the use of the Transport Infrastructure Resilience Indicator (Tiresi). Tiresi ratings complement existing decision-support tools by indicating actions that may be taken to address identified vulnerabilities and improve project robustness. This paper takes stock of the Tiresi methodology and demonstrates the application of its rating system for the case of road infrastructure projects, showing promising accuracy in its predictive power.